International jurisdiction in matter of noncontractual liabillity on the internet: new criteria in determining the place where the harmful event ocurred: Analyzing the STJUE Concurrence vs. Samsung y Amazon, of 21 de december 2016 - Villamarín López, María Luisa (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This article analyzes the new jurisprudential criterion established in December 2016 by the CJEU in the field of torts on the Internet in connection with an infringement of an exclusive distribution contract. The special nature of the legal relationships at stake served in this case to reject the connection criteria used until then as the accessibility and to set as a special forum the place where the reduction in sales was effectively suffered, thus guaranteeing the fulfillment of the purposes pursued by these european rules as well as reducing the risk of forum shopping.
Keywords: Regulation 44/2001 (and 1215/2012); non-contractual liability; place where the harmful event occurred; exclusive distribution contract